Exendin‐4(Lys27PAL)/gastrin/xenin‐8‐Gln: A novel acylated GLP‐1/gastrin/xenin hybrid peptide that improves metabolic status in obese‐diabetic (ob/ob) mice. Issue 3 (19th December 2018) - Hasib, Annie; Ng, Ming T.; Tanday, Neil; Craig, Sarah L.; Gault, Victor A.; Flatt, Peter R.; Irwin, Nigel
Abstract: Background: Therapeutic benefits of peptide‐based drugs is limited by rapid renal elimination. Methods: Therefore, to prolong the biological action profile of the recently characterized triple‐acting hybrid peptide, exendin‐4/gastrin/xenin‐8‐Gln, a fatty acid (C‐16) has been covalently attached, creating exendin‐4(Lys 27 PAL)/gastrin/xenin‐8‐Gln. Exendin‐4/gastrin and liraglutide/gastrin/xenin‐8‐Gln were also synthesized as direct comparator peptides. Results: All hybrid peptides evoked significant concentration‐dependent increases of insulin secretion from isolated murine islets and BRIN‐BD11 cells. Following administration of peptides with glucose to mice, all hybrids significantly reduced the overall glycaemic excursion and increased insulin concentrations. In contrast to other treatments, exendin‐4(Lys 27 PAL)/gastrin/xenin‐8‐Gln displayed impressive antihyperglycaemic actions even 12 hours after administration, highlighting protracted duration of effects. Exendin‐4/gastrin/xenin‐8‐Gln, exendin‐4/gastrin, and exendin‐4(Lys 27 PAL)/gastrin/xenin‐8‐Gln were then progressed to a 31‐day twice‐daily treatment regimen in obese‐diabetic ob/ob mice. All treatments decreased nonfasting glucose and HbA1c concentrations, as well as enhancing circulating and pancreatic insulin levels. Exendin‐4/gastrin and exendin‐4/gastrin/xenin‐8‐Gln also decreased food intake. Glucose tolerance was improved by all treatments, but only exendin‐4(Lys 27 PAL)/gastrin/xenin‐8‐Gln augmented glucose‐induced insulin secretion. Interestingly, treatment regimens that included a xenin component induced clear advantages on the metabolic response to glucose‐dependent insulinotropic polypeptide (GIP) and the glucose‐lowering actions of insulin. Conclusion: This study emphasizes the therapeutic promise of long‐acting, multi‐targeting hybrid gut peptides for type 2 diabetes.